Examining the Relationship between Social Modelling and Physical Activities Involvement - Tero, Darlton-Ace Chan; Biong, Corazon T.; Tero, Juliet C. (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
This study aimed to examine the relationship between social modeling and children’s involvement in physical activities (CIPA) involvement. Descriptive-correlation analysis was utilized to determine the respondents’ profile and the CIPA. Correlation analyses were used to examine relationships between key variables, modelling, and CIPA among 200 randomly selected Grades 1 to 6 pupils in selected randomly private and public schools in the Division of Iligan City. Likert Scale and Inferential Statistics were used to measure the level of self-reported responses. Results showed that all the models influenced the PA, coach ranked first with 88.5% most influential, while peers ranked second 83.5%, parents ranked third 77%, while the lowest influence were teachers 59% which could mean that coach had the highest influence, while teachers were the least influential models. Furthermore, among all the models, Coach Modelling had the closest relationship with the PA involvement. Surprisingly, parents who were supposed to be the first models at home, were not that influential on CIPA because they were too busy doing other things at home or outside their homes, not sports and physical activities.